Grade 11 Students’ English Language Reading Anxiety and its Relationship to Academic Strands and Reading Comprehension Level: Basis for Enhancement Program - Quinal, Kei Jullesse C. (Silliman Journal, 2022)
Comprehension, which is universally understood as the goal of reading and the penultimate “global reading skill,” has been a prime source of inquiry and interest among scholars and experts. However, certain factors which may be caused by an individual’s level in and perception of reading could make comprehension elusive. One of the many unearthed causative factors which could debilitate students’ progress in reading comprehension is anxiety. This study examined the reading anxiety (RA), and reading comprehension (RC) levels of 164 Grade 11 STEAM, ABM, and HUMSS students from Silliman University enrolled in Reading and Writing Skills subject during the school year 2019-2020. Using an adaptation of Zoghi’s English as Foreign Language Reading Inventory (EFLRAI) instrument and practice reading tests from the TOEFL® iBT Reading Practice Questions (2009), the study investigated whether students’ academic strands influence their RA levels and whether or not a relationship exists between their RA and RC level. Results revealed that all strands have a moderate level of RA and a satisfactory level in RC (STEAM-Intermediate level; ABM & HUMSS- High level). Data analysis also disclosed that there is no significant difference between students’ academic strands and their RA level. Finally, RA and RC were found to have a significant positive relationship albeit a weak correlation. This suggests that anxiety does not always have a detrimental effect on students’ RC, but it can be used to students’ advantage. To address this, the researcher proposes a reading enhancement program to equip students with relevant reading strategies and activities that will normalize their anxiety levels